Analysis of Hampden robot arm and designing a three d.o.f prototype robot arm / Mohammad Fadzil Mahassan and Azizee Abdul Aziz - Mahassan, Mohammad Fadzil; Abdul Aziz, Azizee (1994)
This thesis is to analyse the six axes robot arm manufactured by Hampden Inc. in the Instrumentation Laboratory, as it is not functioning according to specifications. From the analysis, two main problems have been identified. The check valve for the pneumatic system is blocked. Hence there is no output air pressure at the outlet The stepper motor for gripper motion causes a voltage drop that effects all the devices and components that use the 12V supply such that they cannot operates. Constructing a three degree of freedom (d.o.f) prototype robot arm starts from the analysis of mechanical parts. After that, the interface circuit, logic circuit and driver circuit have been designed to enable it to control the robot arm using the computer via computer programming